Integrating Islamic Values into Academic Supervision to Support SDG 4: A Multisite Case Study of Teacher Development in Two Faith-Based Primary Schools - Fitria Hanaris; Yatim Riyanto; Nunuk Hariyati; Mohamad Hisyam Ismail; Windasari Windasari; Noer Risky Ramadhani; Hanandita Veda Saphira (Journal of Current Studies in SDGs, 2026)
Objective: To investigate the implementation, operational challenges, and strategic outcomes of integrating prophetic virtues into a standardized instructional coaching framework within faith-based primary schools. Method: Employing a qualitative approach with a multisite case study design, this inquiry examined the academic supervision workflows at School A and School B in Indonesia. Data were generated through prolonged fieldwork triangulation, encompassing semi-structured in-depth interviews with 16 key informants (principals, vice-principals, and teachers), non-participant observations of clinical supervision cycles, and institutional document audits. Data were systematically analyzed using the constant comparative method. Results: The findings demonstrate that transforming the secular GROW model into a spiritually responsive "Prophetic-GROW framework" successfully operationalizes abstract values amanah, lillah orientation, shidq, shura, ta'awun, and tawakkul into structured supervisory behaviors. This framework builds high psychological safety and mitigates evaluation anxiety, resulting in 62.50% of educators at School A and 65.22% at School B achieving "excellent" pedagogical mastery. However, the study identifies a persistent dual-role dilemma where heavy administrative and budgetary duties constrain the principal's coaching time. Novelty: Bridging the empirical gap between secular performance-driven coaching models and theological ethics by developing a comprehensive Prophetic GROW Model for academic supervision. The model demonstrates that integrating Islamic values into coaching creates a supportive psychological climate that enhances teachers' pedagogical competence and professional growth, thereby contributing to SDG 4 (Quality Education) through value-based teacher development and improved educational quality.